OPTIMIZING BROILER CHICKENS PERFORMANCE WITH BOILED SUNFLOWER (Helianthus annuus) SEED MEAL-BASED DIETS: A SUSTAINABLE SOLUTION - Saleh, A. A.; Suleiman, I. O.; Muhammad, H. A.; Dankoli, Z. A.; Rano, N. B. (Fakultas Peternakan, Universitas Padjadjaran, 2024)
The research explored the use of boiled sunflower seed meal (BSSM) as sustainable feed alternative for broiler chickens, evaluating its impact on their growth and development thereby reducing the industry’s reliance on resource-intensive feed ingredients. One hundred and fifty unsexed Ross broiler chicks were used for the study. The experiment was laid in a completely randomized design (CRD) in which BSSM were incorporated in the diets at 0, 10, 20, 30 and 40%, coded as Treatments 1, 2, 3, 4, and 5, respectively. Each treatment comprised of 3 replicates of 10 birds. Birds were housed in floor pens containing wood shavings as litter material. The diets and fresh drinking water were provided ad libitum throughout the eight weeks of the experiment. Data were analysed in statistical analysis system (SAS) package. Results revealed significant differences (p<0.05) in all the growth parameters measured except for initial body weight, feed conversion ratio and mortality. The packed cells volume (PVC) and white blood cells (WBC) were affected (p<0.05) by the treatment effect. Broiler chickens' health and productivity were not negatively affected by 30-40% BSSM inclusion in their diets, suggesting further research on improving sunflower seed using alternative treatment options.